Entrepreneurial Orientation and Sustainable Performance in Indonesian SMEs: Testing a Moderated Mediation Model of Knowledge Management Capability and Environmental Dynamism - Wijaya, Justin; Antonio, Tony; Kouwagam, Adityawarman (Management Analysis Journal, 2026)
This study examines the influence of Entrepreneurial Orientation (EO) on Sustainable Performance (SP) among Indonesian SMEs, incorporating the mediating role of Knowledge Management Capability (KMC) and the moderating role of Environmental Dynamism (ED). Grounded in the Resource-Based View (RBV) and Knowledge-Based View (KBV), the research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) on pilot data from 43 SMEs. The results indicate that EO significantly enhances both KMC and SP, with KMC partially mediating the relationship. However, ED does not significantly moderate the structural relationships. These findings highlight that internal capabilities play a more critical role than external environmental conditions in driving sustainability in SMEs. This study contributes to the literature by integrating EO, KMC, and ED within a moderated mediation framework in an emerging economy context, providing nuanced insights into how entrepreneurial and knowledge-based capabilities interact to support sustainable performance.